Mobile Payment Adoption in Marketing Transactions: A Study of Women Entrepreneurs in Makassar's Retail Sector - Riu, Isma Azis (Abadi Institute, 2025)
This study investigates how women micro-retail entrepreneurs in Makassar adopt and integrate mobile payment systems within their everyday business practices. Using a phenomenological design, the research foregrounds lived experiences to reveal that adoption is neither linear nor purely technology-driven. Instead, it is shaped by functional convenience, trust dynamics, peer-based learning, hybrid cash–digital routines, and the gendered realities of time poverty and informal financial histories. Findings show that while mobile payments offer efficiency, status gains, and expanded customer reach, they also introduce new obligations related to digital recordkeeping, platform management, and risk exposure. Social capital emerges as a critical enabler that accelerates skills acquisition and legitimizes usage, yet interpersonal expectations tied to cash-based norms continue to moderate full transition toward digital payments. The study advances socio-technical and gender-aware interpretations of fintech adoption by integrating TAM, social capital, and behavioral perspectives. Practical implications emphasize the need for platform refinements, modular literacy programs, and community-based training that align with women entrepreneurs’ constraints and relational practices. The research calls for policy frameworks that balance technological innovation with culturally grounded support mechanisms to strengthen inclusive digital financial ecosystems in urban micro-retail markets.